Design Of A Neural Network Based Cervical Cancer Diagnosis System: A Microcontroller Approach. - Tan, Kuan Liung; Mashor, Mohd Yusoff; Mat Isa, Nor Ashidi; Ali, Ahmad Nazri; Othman, Nor Hayati (2003)

(untitled)
Cervical cancer is the second most common type of cancer that affects women,ranked after breast cancer. In Malaysia, there is a shortage of pathologists that can diagnose the disease.